Detailed balance calculations for hot-carrier solar cells: coupling high absorptivity with low thermalization through light trapping - Giteau Maxime; Suchet Daniel; Collin Stéphane; Guillemoles Jean-François; Okada Yoshitaka (EPJ Photovoltaics, 2019)
Hot-carrier solar cells could enable an efficiency gain compared to conventional cells, provided that a high current can be achieved, together with a hot-carrier population. Because the thermalization rate is proportional to the volume of the absorber, a fundamental requirement is to maximize the density of carriers generated per volume unit. In this work, we focus on the crucial role of light trapping to meet this objective. Using a detailed balance model taking into account losses through a thermalization factor, we obtained parameters of the hot-carrier population generated under continuous illumination. Different absorptions corresponding to different light path enhancements were compared. Results are presented for open-circuit voltage, at maximum power point and as a function of the applied voltage. The relation between the parameters of the cell (thermalization rate and absorptivity) and its characteristics (temperature, chemical potential, and efficiency) is explained. In particular, we clarify the link between absorbed light intensity and chemical potential. Overall, the results give quantitative values for the thermalization coefficient to be achieved and show that in the hot-carrier regime, absorptivity enhancement leads to an important increase in the carrier temperature and efficiency.